2016
DOI: 10.1152/ajpregu.00346.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-linolenic acid supplementation alters skeletal muscle plasma membrane lipid composition, sarcolemmal FAT/CD36 abundance, and palmitate transport rates

Abstract: The cellular processes influenced by consuming polyunsaturated fatty acids remains poorly defined. Within skeletal muscle, a rate-limiting step in fatty acid oxidation is the movement of lipids across the sarcolemmal membrane, and therefore, we aimed to determine the effects of consuming flaxseed oil high in α-linolenic acid (ALA), on plasma membrane lipid composition and the capacity to transport palmitate. Rats fed a diet supplemented with ALA (10%) displayed marked increases in omega-3 polyunsaturated fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
5
20
0
Order By: Relevance
“…permeability and fluidity of membranes) and overall health status. In rats, dietary ALA supplementation increased the movement of lipids across the sarcolemmal membrane, a rate-limiting step in fatty acid oxidation, and led to higher triglyceride content and rates of fat oxidation 71 , while it is known to have antioxidant and anti-inflammatory effects in both rats and humans 72 . However, the use of the products evaluated in this study in finishing diets for adult gilthead sea bream farmed on diets with high substitution of FM and FO is worthy to be also explored.…”
Section: Discussionmentioning
confidence: 99%
“…permeability and fluidity of membranes) and overall health status. In rats, dietary ALA supplementation increased the movement of lipids across the sarcolemmal membrane, a rate-limiting step in fatty acid oxidation, and led to higher triglyceride content and rates of fat oxidation 71 , while it is known to have antioxidant and anti-inflammatory effects in both rats and humans 72 . However, the use of the products evaluated in this study in finishing diets for adult gilthead sea bream farmed on diets with high substitution of FM and FO is worthy to be also explored.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose transporter 4 expression was also down regulated in both C18:3 and C16:1 supplemented lambs. Chorner et al (2016) also reported that α-linolenic acid supplementation may result in increased intramuscular lipid content and whole body fat due to the greater rate of lipid transport (FATP and FAT/CD36). In a study of Oliveira et al (2014), the greater C18 fatty acid content in a soybean diet was responsible for greater expression of LPL and FABP4.…”
Section: Marblingmentioning
confidence: 97%
“…Expression of CD36 induces the accumulation of conjugated linoleic acids (CLA) in human macrophages and 15P-1 cell lines (testicular cells) of mice [34,35]. Similarly, CD36 protein expression is increased upon feeding ALA enriched diets to rats promoting the transport of lipids into their resting skeletal muscles [36]. This information suggests that CD36 is actively involved in the uptake of FAs in mammalian cells.…”
Section: Effects Of Nefas On Gc Functionmentioning
confidence: 99%